Bosonic spinons in anisotropic triangular antiferromagnets - Youngsu Choi (Nature Portfolio, 2021)
Spinons are quasisparticles that can appear in anisotropic triangular lattices, however, probing the statistics and dynamics of such excitations is experimentally challenging. Here, Choi et al present Raman spectroscopy measurements of anisotropic triangular lattices, showing a bosonic evolution of the spinon scattering.